REJUVENASI POLITIK ALIRAN MAHASISWA PERGURUAN TINGGI IAIN TULUNGAGUNG DALAM PILPRES 2019 - Idha Ratnawati, Nency Puput; Ali Azhar, Muhammad; -, Bandiyah (Jurnal Nawala Politika, 2021)
This study reveals the existence of the political flow of the Kyai, Santri, and Abangan communities in IAIN Tulungagung state university and its relationship in influencing student voting behavior in the 2019 General Election. The results of this study indicate that tertiary institutions can be labeled non-neutral because they carry and apply the identity of a certain group openly, resulting in discrimination against minority groups. In addition, the findings obtained are practical political practices that have entered the realm of educational institutions. Campus officials, lecturers, religious teachers, and administrators of campus / Ma'had Islamic boarding schools such as Kyai, even students and their families, are considered vulnerable to become easy targets for political actors to gain votes. Kyai and university officials are considered to have an important role in guiding the political choices of students / students when general elections take place.   Keywords: Political Flow, Kyai, Santri, Abangan, Voting Behavior